The comparison of catastrophic health expenditure and its inequality between urban and rural households in China - Xian-zhi Fu (Health Economics Review, 2022)
Background: In recent years, the goal of universal coverage of the basic medical insurance schemes has been basically achieved in China, but the heavy economic burden of diseases is still the main cause of poverty in many households. Exploring catastrophic health expenditure (CHE) and its inequality are highly important for forward- looking policymaking. This study aims to compare the incidence, intensity and inequality of CHE between urban and rural households in China. Methods: This study was based on a national representative household survey-the China Family Panel Studies (CFPS)-that was conducted from 2012 to 2018. Concentration index (CI) was employed to measure the inequality of CHE incidence and overshoot, while the decomposition method of the CI was used to estimate the main influencing factors affecting inequality of CHE incidence. Results: From 2012 to 2018, the CHE incidence of urban households increased from 11.01 to 11.88%, while the CHE incidence of rural households decreased from 18.42 to 18.31%. During the same period, the CI of CHE incidence for urban households decreased from - 0.1480 to - 0.1693, while that for rural households declined from - 0.1062 to - 0.1501. The major contribution to the pro-poor inequality in CHE incidence was associated with socioeconomic status, lagged CHE, receiving inpatient services, having elderly members, education of household head, and self- assessed health status of household head. Conclusions: Rural households had higher risk of incurring CHE than urban households. The strong pro-poor inequality for CHE incidence and overshoot could be found in both two groups. The problem of poverty due to illness was more severe among low-income groups in rural areas than in urban areas. The relevant policy interventions should further focus on encouraging the development of supplementary medical insurance and increasing the reimbursement rate for hospitalization expenses in the medical assistance system.
Keywords: 330; Catastrophic health expenditure; Inequality; Concentration index; Decomposition